Energy shocks in the Euro area: disentangling the pass-through from oil and gas prices to inflation - Chiara Casoli; Matteo Manera; Daniele Valenti (Fondazione Eni Enrico Mattei (FEEM), 2022)
We develop a Bayesian Structural VAR (SVAR) model to study the relationship between different kinds of energy shocks and inflation dynamics in Europe. Specifically, we include in our specification two separate energy markets (oil and natural gas) and two target macroeconomic variables, measuring inflation expectations and the realized headline inflation. Our results demonstrate that, during the last year, inflation in the Euro area is more affected from energy price shocks, particularly those coming from the natural gas sector. The high peaks of the Eurozone inflation are mainly associated with gas consumption demand shocks and, to a lesser extent, to oil and gas supply shocks.
Keywords: C11; E31; Q41; Q43; 330; Energy shocks; Oil and gas markets; Inflation; Bayesian Structural VARs